Estimation of Blood Glucose Levels Using a Non- Invasive Infrared-Based Optical Sensor: A Pilot Study - Husneni Mukhtar; Muhammad Mugni Zaelani; Muhammad Rafy Nasrullah; Hesty Susanti (Engineering Science Letter, 2025)
Blood glucose measurement is critical to diabetes management and prevents chronic complications such as neuropathy, nephropathy, and retinopathy. However, current methods are invasive, uncomfortable, and costly. Although several non-invasive approaches have been explored, no commercially available device offers a simple, affordable, and user-friendly solution for non-invasive blood glucose estimation, particularly one suitable for self-measurement outside clinical settings. This underscores the need for practical and inclusive alternatives. This study aimed to develop and evaluate a blood glucose estimation device using infrared LEDs to measure light transmittance through the fingertip. The research was conducted in two stages: initial testing using glucose solutions with varying concentrations (0.02, 0.06, 0.10, and 0.20 g/ml) and added red dye (0.05, 0.10, and 0.15 ml) to validate the sensor's response, followed by direct validation on human fingers against commercial blood glucose test strip readings. The results showed a strong positive correlation between sensor output and glucose levels, with a Pearson correlation coefficient of r = 0.995. Using a regression-based calibration model, the system achieved a mean absolute error (MAE) of 1.63 mg/dL, and a root mean square error (RMSE) of 1.72 mg/dL. Cross-validation, such as Bland-Altman analysis and Clarke Error Grid, was conducted to verify model robustness. These preliminary results suggest that the developed system holds strong potential as a simple, affordable, and non-invasive tool for blood glucose self-monitoring, especially in resource-limited settings. However, further validation on larger, more diverse populations is necessary.